INVESTIGATING ESP STUDENTS’ RESPONSES ON THE LECTURER-APPLIED GAMIFICATION STRATEGIES - Sukci, L. Bening Parwita (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2025)
This study was geared by previous research that covered the effectiveness of the application of gamification concepts in English for Specific Purposes classes in university level. Gamification has been considered relevant in growing and maintaining students’ learning motivation, as most research focused on how lecturers applied the concepts of gamification and the results of the processes on students. This research will scrutinize how students respond to the lecturer’s application of the gamification elements in class. This study uses a questionnaire on how students perceive the use of gamification elements in class and how it helps them improve their self-confidence. The results of this research show that students were aware of the gamification strategies applied in class activities and they responded positively to the application of gamification elements in their ESP classes. Most of them agreed that gamification helped motivate them to relax and be more engaged in class activities as it improved their self-confidence in using English. Keywords: students’ self-confidence, gamification, ESP, learning motivation.